Foveolar Müller cells of the Pied Flycatcher: morphology and distribution of the intermediate filaments regarding the cell transparency - Zueva, Lidia (Microsc Microanal, 2016)
The specialized intermediate filaments (IFs) have critical importance for the clearness and uncommon transparency of the vertebrates' lens fiber cells, although the physical mechanisms involved are poorly understood. Recently, an unusual low-scattering light transport was also described in the retinal Müller cells. Exploring the function of the IFs in the Müller cells, we have studied the morphology and distribution pattern of the IFs and other cytoskeletal filaments inside the Müller cell main processes in the foveolar part of the avian (Pied Flycatcher) retina. We found that some IFs surrounded by globular nanoparticles (that we suggest are crystallines) are present in almost every part of the Müller cells that span the retina, including the microvilli. Unlike the IFs implicated in the mechanical architecture of the cell, these IFs are not connected to any specific cellular membranes. Instead, they are organized into bundles, passing inside the cell from the endfeet to the photoreceptor, following the geometry of the processes and repeatedly circumventing numerous obstacles. We believe that all of the presently reported data effectively confirms that the model of nanooptical channels built of the intermediate filaments [Makarov et al., 2015, Khmelinskii et al., 2015] may provide a viable explanation of the Müller cell transparency.